SYSTEM ANALYSIS AND MODERN METHODS OF CONFLICTS IN MANAGEMENT - TYMCHAK, Vira (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the importance of system analysis as a key indicator of efficiency of conflict resolution in management. The identification of conflicts that can negatively affect the management process is generalised. The main features and modern methods of conflicts that should be taken into account in the business environment are defined. It has been researched that the systemic analysis of conflicts in management is based on an integrated approach to their definition and the main stages of such analysis are identification of the main causes of conflict, determination of the type, assessment of the impact of conflict on the organisation, identification of conflict, monitoring and selection of the optimal strategy for their management. It is analysed that the practical application of system analysis for managers will allow creating a flexible management system that takes into account factors of the external and internal environment. It will also ensure the effectiveness of modern methods, in particular, conflict mapping, SWOT analysis, computer content analysis to achieve a positive result and resolve conflict situations.